Grid Island Energy Transition Scenarios Assessment Through Network Reliability and Power Flow Analysis - Hussain, E. K.; Thies, Philipp R.; Hardwick, Jon; Connor, Peter M.; Abusara, Mohammad (Frontiers in Energy Research, 2021)
This paper presents a methodology for the reliability and power flow analysis of island or off-grid power networks for situations of scarce data and information and offers a pragmatic approach to derive the required power network information, including the power cable parameters and the load at each power node. The paper aims to present the general methodology, and to illustrate its application, using Ushant Island as a case study. The assessment of the current power network status and the reliability analysis are presented. Grid performance parameters are further compared for conventional diesel generator operation and renewable energy generation scenarios to demonstrating the advantages of replacing the existing diesel units with renewable energy sources in terms of system reliability. The analysis shows that by introducing renewable energy systems to the island’s grid, the reliability of the grid increases by up to 50% and cable capacity usage reduces by up to 30%. Furthermore, this work suggests that it would not be necessary to modify the grid cables when substituting the diesel generator. The paper will be of interest to network planners, community stakeholders, project developers and decision-makers concerned with renewable energy investment on islands and in remote rural areas.